The first international consensus on mucous membrane pemphigoid: definition, diagnostic criteria, pathogenic factors, medical treatment, and prognostic indicators. - Chan, L; Ahmed, A; Anhalt, G; Bernauer, W; Cooper, K; Elder, M; Fine, J; Foster, C; Ghohestani, R; Hashimoto, T; Hoang-Xuan, T; Kirtschig, G; et al. (2002)
OBJECTIVE: We aimed to develop consensus-based recommendations for streamlining medical communication among various health care professionals, to improve accuracy of diagnosis and treatment, and to facilitate future investigations for mucous membrane pemphigoid. PARTICIPANTS: Because of the highly specific nature of this group of diseases, the 26 invited participants included either international scholars in the field of mucous membrane pemphigoid or experts in cutaneous pharmacology representing the 3 medical disciplines ophthalmology, oral medicine, and dermatology. EVIDENCE: The first author (L.S.C.) conducted a literature search. Based on the information obtained, international experts who had contributed to the literature in the clinical care, diagnosis, and laboratory investigation for mucous membrane pemphigoid were invited to participate in a consensus meeting aimed at developing a consensus statement. CONSENSUS PROCESS: A consensus meeting was convened and conducted on May 10, 1999, in Chicago, Ill, to discuss the relevant issues. The first author drafted the statement based on the consensus developed at the meeting and the participants' written comments. The draft was submitted to all participants for 3 separate rounds of review, and disagreements were reconciled based on literature evidence. The third and final statement incorporated all relevant evidence obtained in the literature search and the consensus developed by the participants. The final statement was approved and endorsed by all 26 participants. CONCLUSIONS: Specific consensus-based recommendations were made regarding the definition, diagnostic criteria, pathogenic factors, medical treatment, and prognostic indicators for mucous membrane pemphigoid. A system of standard reporting for these patients was proposed to facilitate a uniform data collection.